Effectiveness of Online Versus Telephone Counseling of Rational-Emotional-Behavioral Therapy on Sexual Function of Women Undergoing Cardiac Rehabilitation: A Randomized Clinical Trial: - Memar, Fatemeh Zahra; Farajkhoda , Tahmineh; Khanabadi, Mahdi; Sarebanhassanabadi, Mohammadtaghi (Galen Medical Journal, 2022)
Background: Sexual function in patients with cardiovascular disease (CVDs) is often associated with anxiety and irrational beliefs. Moreover, 60-78% of patients with CVDs report sexual problems. Some studies suggest that sexual counseling is necessary for these patients but is not usually provided for them. Online or telephone counseling may be helpful during the covid-19 pandemic, but studies on its application to sexual function appear to be limited. This study aimed to investigate the effectiveness of online vs. telephone counseling of rational-emotional-behavioral therapy (REBT) on the sexual function of women undergoing cardiac rehabilitation. Materials and Methods: In this randomized clinical trial study, 46 women diagnosed with CVDs under rehabilitation were assigned into online and telephone groups. Overall, eight 60-min intervention sessions were held (once a week). The Female’s Sexual Function Index (FSFI) questionnaire was completed by the women at baseline, week 8th, and follow-up week 12th (main outcome). Results: FSFI scores between the two groups at baseline (online: 13.28Â±2, telephone: 12.68Â±1.52, P=0.254) compared to week 12th (online 28.86Â±2.44, telephone, 26.6Â±2.10, P=0.002) were significantly different. As for within-group comparison in baseline compared to week 12th statistically significant difference was observed in all subscales of FSFI (P<0.05). Conclusion: Online and telephone REBT counseling can improve the sexual function of women undergoing cardiac rehabilitation, but online counseling appears to be more effective. Thus, this method is recommended to improve the sexual function of these women during the covid-19 pandemic